Report on the Dutch Consensus Development Meeting for Implementation and Further Development of Population Screening for Colorectal Cancer Based on FOBT - M. de Visser; M. van Ballegooijen; S. M. Bloemers; S. J. H. van Deventer; J. B. M. J. Jansen; J. Jespersen; C. Kluft; G. A. Meijer; J. Stoker; G. A. de Valk; M. F. Verweij; F. A. Vlems (Cellular Oncology)
A consensus development meeting was held to evaluate whether or not in the Netherlands all requirements were fulfilled for implementation of population screening with FOBT for colorectal cancer, or whether consensus was present that fulfilment by additional research or organisational actions could be obtained within 2–3 years. There was consensus that all classical Wilson and Jungner (1968) criteria, and six additional ones added more recently, had already been fulfilled or could be fulfilled within 2–3 years. Consequently, it was concluded that a national population screening for colorectal cancer should be implemented and carried out in the Netherlands in line with current national and European cancer screening programmes. A list of organisational actions to be taken was established. Research that is needed before the actual national launch of the screening within 2–3 years has been defined. Priorities have to be set for research and organisational actions for the coming 2–3 years for the implementation of population screening. In addition, research suggestions have been defined for the next 10–15 years for evaluation and/or improvement of implemented FOBT screening, and for future screening methodology. It was considered essential that infrastructure for future research would be embedded in the screening programme. A project group to arrange this should be formed.